Análisis de calidad en los bares de segunda categoría cantón Loja - Mazón Sotomayor, Juan Francisco (2024)
This research paper, called "Analysis of Service Quality in Second-Category Bars in the City of Loja," aims to evaluate the quality of service provided by second-category bars in Loja, Ecuador. The study employs a quantitative approach, utilizing surveys administered to specific customers to gather data through sampling techniques. Tabulation of the survey results allows for a closer examination of the primary objective: assessing service quality in second-category bars in Loja. Direct observation serves as the methodological approach, enabling the identification of characteristics essential for determining aspects of service quality within these establishments. The study establishes three specific objectives: the first one is to observe the quality of service in second-category bars; the second one is to analyze the perception of service provided in second- category bars in Loja, and the third one is to establish a plan for improvement in areas where bars be inadequate in terms of quality. To achieve the first objective, the MINTUR checklist was employed as a tool to guide the evaluation process. For the second objective, the SERVQUAL model was utilized to analyze customer expectations and perceptions regarding the establishments. Finally, to address the third objective, a SWOT analysis was conducted to identify the strengths, weaknesses, opportunities, and threats faced by the bars. Subsequently, a cross-SWOT analysis was performed to generate strategies, which were then incorporated into a customized improvement plan to address the identified deficiencies of the establishments.